Homologous tumor cell membrane-encapsulated methyl 5-aminolevulinate solid lipid nanoparticles for the precise localization of melanoma and sensitization by radiotherapy - Yanyan Meng; Shaoqing Chen; Pengyin Li; Cheli Wang; Xinye Ni (Materials & Design, 2024)
Melanoma is a highly invasive and lethal skin cancer with a strong tendency to metastasize and has a poor prognosis. Radiotherapy is one of the important treatments for melanoma. In this study, monoglyceride solid lipid nanoparticles (MG SLNs) were wrapped with the B16-F10 cell membrane (B16 CM) for the fabrication of B16@MG. B16@MG had low toxicity and specifically targeted B16-F10 cells. B16-F10 tumor–bearing mouse model showed that indocyanine green (ICG) -loaded B16@MG achieved long-term accumulation in the tumor and facilitated the localization of the tumor boundary. MG SLNs were encapsulated with methyl 5-aminolevulinate (MLA) and desferrioxamine (DFO), and B16 CM was wrapped around their surfaces to obtain B16@MG–MLA–DFO.MLA was metabolized to protoporphyrin IX (PpIX) in the cells and DFO reduced the content of iron ion in the cells, blocked the biotransformation of PpIX, and promoted the accumulation of PpIX in the cells. The results of mitochondrial reactive oxygen species (ROS) and membrane potential detection showed that PpIX enhanced the generation of ROS, caused DNA and mitochondrial damage, and led to the apoptosis of tumor cells under radiotherapy. In B16-F10 tumor–bearing mice, B16@MG–MLA–DFO can improve the efficacy of radiotherapy and allow the integration of diagnosis and treatment.